The experiences of palliative lung cancer patients participating in a clinical trial. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Sivell, Stephanie; Noble, Simon; Harrop, Emily; Byrne, Anthony; Moore, Barbara; Nelson, Annmarie
Abstract : Background: Palliative care lung cancer patients are under-represented in oncology trials and very little is understood about their experiences of participating in clinical trials. FRAGMATIC is the largest lung cancer study in the UK and is investigating the effects of Fragmin (a self-injected anticoagulant) in patients with lung cancer. This current study (QUALFRAG) is a qualitative substudy of the FRAGMATIC trial. Aims: To explore patients' experiences of participating in FRAGMATIC and the impact on quality of life, while at the same time collecting data on patients' experiences of advanced lung cancer. Methods: Semistructured interviews will be held with two groups of 6–10 patients (12–20 patients in total) recruited from the intervention and control arms of the FRAGMATIC trial. Analysis: Interviews will be analysed using Interpretative Phenomenological Analysis (IPA) to identify emergent themes that reflect participants' lived experience. Results: Data will be presented on patients' experiences of participating in the FRAGMATIC study, symptom progression and (where relevant) how tolerable Fragmin is. Conclusions: The results of this study will help future studies target appropriate symptom control issues in palliative lung cancer patients and inform future healthcare management with respect to the treatment and prevention of cancer associated thrombosis.